Affects, resources, culture and perceived health: what is the relationship among them? - Merino, Mª Dolores; Privado, Jesús; Gracia, Zeus (Anales de Psicología / Annals of Psychology, 2017)
The purpose of this research is to understand if the relationship between positive and negative affect (PA/NA) and perceived health is mediated by psychosocial resources, and, whether culture (collectivistic vs. individualistic) has a role in that relationship. Structural Equation Models were applied: The first expressed the direct and indirect relationship PA/NA to health. The second reflected indirect influence of PA/NA on health and, resources mediated between both. Both models were tested in two cultures: one individualistic (Spain) and the other collectivistic (Mexico). The results showed that models work differently in both cultures. In Spain there were no significant differences between the two models. In Mexico, the direct and indirect relationship model functions better. These results have interesting implications: The influence of PA/NA on health could be different depending on the culture, so, future research to reconsider the cultural variable, would be interesting. The way PA vs. NA influences perceived health is different; PA can influence directly and indirectly, through psychosocial resources, while NA can only influence directly. It would be fascinating if future research would replicate this, including more countries, and, using biological measurements of health.